The future of the world : futurology, futurists, and the struggle for the post-Cold War imagination - Andersson, Jenny, 1974- 1974- (Oxford University Press, 2018)
'The Future of the World' is devoted to the intriguing field of study which emerged after World War Two, futurism or futurology. Jenny Andersson explains how futurist scholars and researchers imagined the Cold War and post Cold War world and the tools and methods they would use to influence and change that world. Futurists were a motley crew of Cold War warriors, nuclear scientists, journalists, and peace activists. Some argued it should be a closed sphere of science defined by delimited probabilities. They were challenged by alternative notions of the future as a potentially open realm. Futurism also drew on an eclectic range of repertoires, some of which were deduced from positivist social science, mathematics, and nuclear physics, and some of which sprung from alternative forms of knowledge in science fiction, journalism, or religion